Epidemiological data of an influenza A/H5N1 outbreak in elephant seals in Argentina indicates mammal-to-mammal transmission - Uhart, Marcela M. (2024)
H5N1 high pathogenicity avian influenza virus has killed thousands of marine mammals in South America since 2022. Here we report epidemiological data and full genome characterization of clade 2.3.4.4b H5N1 HPAI viruses associated with a massive outbreak in southern elephant seals (Mirounga leonina) at Península Valdés, Argentina, in October 2023. We also report on H5N1 viruses in concurrently dead terns. Our genomic analysis shows that viruses from pinnipeds and terns in Argentina form a distinct clade with marine mammal viruses from Peru, Chile, Brazil and Uruguay. Additionally, these marine mammal clade viruses share an identical set of mammalian adaptation mutations which were also present in tern viruses. Our combined ecological and phylogenetic data support mammal-to-mammal transmission and occasional mammal-to-bird spillover and suggest multinational transmission of H5N1 viruses in mammals. We reflect that H5N1 viruses becoming more evolutionary flexible and adapting to mammals in new ways could have global consequences for wildlife, humans, and/or livestock.